Understanding the Determinants of User Continuance Intention on Indonesia's E-Government Web Portal - Tommy Putra Pratama Gunawan; Irni Irmayani; Dana Indra Sensuse; Sofian Lusa; Nur Indrawati (Eduvest - Journal of Universal Studies, 2026)
This current research seeks to explore various factors that can influence the sustainable use of SIPPN, as an Indonesian national public service information portal. The quantitative PLS-SEM approach was adopted for the research with 140 user respondents across Indonesia. This research uses Information Quality, Efficiency, Accessibility, Service, System performance, Design and Usability, Citizen Participation, Quality Perception, Citizen Satisfaction and User Intention as the factors. As per analysis results, Efficiency, System Performance and Citizen Participation have a significant influence on Quality Perception and Citizen Satisfaction. Quality Perception and Citizen Satisfaction have a high impact on user intention to continue the use of the SIPPN portal. Study findings confirm SIPPN as an established strategic national public information portal comparable to other similar portals at international level.  To make the portal more efficient, inclusive and a global-standard one-stop national public service information portal, its interoperability and user feel must improve, as well as system performance.